Numerical study on the trajectory of dropped cylindrical objects. (15th January 2017) - Xiang, Gong; Birk, Lothar; Yu, Xiaochuan; Lu, Haining
Abstract: Dropped objects are among the top ten causes of fatalities and serious injuries in the oil and gas industry(DORIS, 2016) . Objects may be dropped during lifting or any other offshore operation. Concerns for health, safety, and the environment (HSE) as well as possible damage to structures require the prediction of where and how a dropped object moves underwater. In this paper, the authors propose a new three-dimensional (3D) theory which considers the effect of axial rotation on dropped cylindrical objects. The 3D method is based on a modified slender body theory for maneuvering. A numerical tool called Dropped Objects Simulator (DROBS) has been developed based on this 3D theory. Firstly, simulated results of a dropped drilling pipe model using a 2D theory byAanesland (1987) are compared with results from 3D theory when rolling frequency is zero. Good agreement is found. Further, factors that affect the trajectory, such as drop angle, normal drag coefficient, binormal drag coefficient and rolling frequency are systematically investigated. It is found that drop angle, normal drag coefficient and rolling frequency are the three most critical factors determining the trajectories. Finally, a low rolling frequency case is studied. Plots of landing points at the bottom of a 5 m deep water tank are obtained by investigating a series of simulations with different drop angles from 0° to 90° . Highlights: The newly-developed 3D theory effectively discloses the physical mechanism used to describe the trajectory of dropped cylindrical objects. The numerical tool 'DROBS' based on this 3D theory can efficiently predict the 3D trajectory of cylindrical object dropped into the sea. Drop angle and normal drag coefficient are the two most critical factors determining the trajectories. The rolling frequency greatly affect the trajectory of dropped cylindrical objects. Excursion distribution have been calculated and validated by experimental tests, which meets the demand from the industry.